Logistics Solutions to Container Congestion Problems in Port Sudan 2020 - 2024 (Theoretical Study) - Abdelgadir, Somaia Osman Mohamed; Ahmed, Ahmed Osman Ibrahim (Journal of Ecohumanism, 2025)
This theoretical study focused on addressing and explaining the problem of container congestion and overcrowding in Port Sudan, the main port of Sudan, which necessitates finding solutions to this problem that has negatively affected the movement of exports and imports. Especially since the Republic of Sudan is witnessing many disturbances as a result of the popular revolution that changed the regime, which created many challenges in this transitional period that Sudan is experiencing as a result of the change of regimes and thus its impact on the administrative and financial system in various joints of the state apparatus. The study proposed a model to simulate the situation, which was applied and introduced to stakeholders. The study concluded with a number of results, perhaps the most important of which are: There is a large congestion and overcrowding in the container area, as well as logistical and administrative obstacles that increase the size of the problem, and also from the results of the study that this congestion necessarily leads to an increase in handling, loading and unloading costs. The study concluded with a set of recommendations, the most important of which are: the necessity of formulating clear strategies and policies from the port administration to deal with this deteriorating reality of services, as well as studying the experiences of countries that suffer from similar conditions to learn how to overcome these problems.